Why output rises faster than employment in the service sector of India? - Prakash, Dipak (Economic and Political Weekly)
India$1 (Bs exceptional growth pattern after the 1980s is attributed to the robust growth of the service sector. The growth pattern of services is not homogeneous and uniform. However, it is spearheaded largely by modern services than traditional ones and is more K-intensive than labour-intensive service. India$1 (Bs service sector is no exception to modern services-led growth owing to rising capital intensity and the worldwide phenomenon of technology-biased growth. Further, these transitions in the services have a direct bearing on employment generation.- Reproduced s